Combining Network Pharmacology, Molecular Docking, Molecular Dynamics Simulation, and Experimental Validation to Uncover the Efficacy and Mechanisms of Si-Miao-Yong-An Decoction in Diabetic Wound Healing - Zhang S; Shao Y; Jin R; Ma B (Journal of Inflammation Research)
Shujuan Zhang,1,* Yiming Shao,2,* Ranran Jin,2 Baodong Ma2 1Department of Laboratory Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, People’s Republic of China; 2Center of Stem Cell and Regenerative Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Baodong Ma, Center of Stem Cell and Regenerative Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, No. 16, Tongbai North Road, Zhengzhou, Henan, 450000, People’s Republic of China, Email zxyymbd@163.comPurpose: Si-Miao-Yong-An (SMYA) Decoction, a traditional Chinese herbal mixture, shows promise for managing diabetic complications. Up to this point, no reports have explored the effects of SMYA on diabetic wounds or the underlying mechanisms. This study aimed to investigate the therapeutic potential of SMYA in promoting diabetic wound healing and to elucidate the underlying molecular mechanisms.Methods: The wound healing effects of SMYA were evaluated in db/db diabetic mice by measuring wound closure rates and histological characteristics, including epidermal thickness and collagen deposition. Network pharmacology was utilized to identify active ingredients and corresponding therapeutic targets of SMYA, followed by validation through molecular docking and molecular dynamics simulations. KEGG and GO enrichment analyses were conducted to elucidate the relevant biological processes and pathways. In vitro studies involving high-glucose-treated HUVECs assessed the effects of SMYA-containing serum on cellular migration and angiogenesis. Finally, the expression of inflammatory factors and RAGE in the wound tissue was detected by qRT-PCR.Results: SMYA significantly accelerated wound closure in db/db mice, as evidenced by improved epidermal thickness, tissue morphology, and collagen deposition. Network pharmacology identified 140 overlapping genes involved in angiogenesis and inflammation, with the AGE-RAGE signaling pathway playing a central role. Molecular docking and dynamics simulations revealed strong binding stability of quercetin and kaempferol to inflammation-related hub targets, including IL-6, TNF, and IL-1β. In vitro, SMYA-containing serum alleviated high-glucose-induced impairments in HUVEC migration and angiogenesis. Furthermore, qRT-PCR analysis showed that SMYA significantly downregulated Tnf, Il1b, Il6, and Rage expression in wound tissues, supporting its anti-inflammatory effect.Conclusion: SMYA promotes diabetic wound healing by modulating the inflammatory microenvironment and inhibiting the AGE-RAGE signaling pathway. These findings provide robust evidence for SMYA’s therapeutic potential and lay a foundation for its future clinical application in treating diabetic wounds.Keywords: Si-Miao-Yong-An decoction, diabetic wound, network pharmacology, molecular docking, molecular dynamics simulation, inflammation